2019
DOI: 10.3390/su11236652
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem Model Proposal in the Tourism Sector to Enhance Sustainable Competitiveness

Abstract: Service companies in developed countries represent 70–80% of the Gross Domestic Product (GDP). In Spain, within the service sector, tourism is the main contributor and is growing annually. This is obviously an opportunity for the country due to its benefits and economic effects but at the same time a well-structured, sustainable and competitive model for its continued development is needed in order to adopt best practices and reference innovative models from other sectors. A qualitative approach using Case Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 16 publications
2
23
0
Order By: Relevance
“…With the advancement of human society, the assessment of tourism competitiveness cannot be based only on primary consideration on tourism performance and competitive advantages, but from a more progressive insight. In particular, how to promote the sustainable tourism competitiveness through enhancing entrepreneurship ecosystem [27], constructing the positive relationships between the government and tourism development [43], and optimizing business management environment [3,4,25,26,44] has become a meaningful research issue, which leads to the suitable measures, and a conceptual framework utilized to evaluate a tourist destination competitiveness requires a critical investigation of the literature to identify the sufficient reinforcement of information on the destination business environment (DBE) and destination competitive advantages (DCA). That is, the determinants that affect the competition level of tourism destinations must be essentially related to the competitiveness of tourism-related constituent firms and based on the generic business strategy views identified by Porter [42], Miles and Snow [14], and Stevenson and Jarillo [15].…”
Section: Tourism Competitiveness and Its Applicationsmentioning
confidence: 99%
See 4 more Smart Citations
“…With the advancement of human society, the assessment of tourism competitiveness cannot be based only on primary consideration on tourism performance and competitive advantages, but from a more progressive insight. In particular, how to promote the sustainable tourism competitiveness through enhancing entrepreneurship ecosystem [27], constructing the positive relationships between the government and tourism development [43], and optimizing business management environment [3,4,25,26,44] has become a meaningful research issue, which leads to the suitable measures, and a conceptual framework utilized to evaluate a tourist destination competitiveness requires a critical investigation of the literature to identify the sufficient reinforcement of information on the destination business environment (DBE) and destination competitive advantages (DCA). That is, the determinants that affect the competition level of tourism destinations must be essentially related to the competitiveness of tourism-related constituent firms and based on the generic business strategy views identified by Porter [42], Miles and Snow [14], and Stevenson and Jarillo [15].…”
Section: Tourism Competitiveness and Its Applicationsmentioning
confidence: 99%
“…Compared with tourist perspective, it is more convincing to analyze destination competitiveness from a business perspective, which is supportive because the various stakeholders with rich tourism business experience are the real specialists in formulating accurate decisions and assessing objective investment conditions while complying with local regulations [45,48]. The most recent research demonstrated that the sustainable destination management inputs and competitiveness are inseparable from technology innovation, business management environment, entrepreneurship, and government supports [18,[25][26][27]43,44,49].…”
Section: Tourism Competitiveness From the Perspective Of The Businessmentioning
confidence: 99%
See 3 more Smart Citations